The development of speaking skills in 8th grade students at ¨Rolando Pedrosa Fernández¨ Secondary School - Hernández Manduca, Anniel (Universidad Central "Marta Abreu" de Las Villas, 2017)
This major paper carried out a deep research into the theory of the communicative language teaching of English in the present Cuban Secondary Schools, specifically in the development of the speaking skills in the English language in eighth grade. The students from this level at the end of the grade should communicate by themselves in brief and simple messages about personal life and their preferences according to the Cuban context. The teaching of English in the Secondary School helps the students to develop communicative skills that allow them to be able to understand and assimilate the language, and to communicate among them in a simple way. This research was carried out at “Rolando Pedrosa Fernández” Secondary School in Báez, Placetas, where the author works, and for the effects of this research a study group was used, which served for the diagnosis and for the development of the building-up process. To carry out this research different instruments and techniques were administered. The practical implementation of some communicative exercises to develop the speaking skills in eighth grade students was carried out and it showed positive results in the students, attaining the objectives for what they were originally designed. Taking into account the elements previously explained, a complementary manual was designed to gather all the exercises that were created throughout the academic course to help the students to put into practice the contents learned in classes. This work consists of six parts: Introduction, Main Part, Conclusions, Recommendations, Bibliography and Annexes.

El siguiente trabajo investigativo llevó a cabo una investigación profunda en la teoría sobre la enseñanza comunicativa del inglés como lengua extranjera en las escuelas secundarias básicas cubanas actualmente, específicamente en el desarrollo de las habilidades de expresión oral en la lengua inglesa en los estudiantes de 8vo grado. Los estudiantes de este nivel al finalizar el curso deben comunicarse por ellos mismos mediante mensajes cortos y simples acerca de su vida personal y sus preferencias de acuerdo al contexto cubano. La enseñanza del inglés en Secundaria Básica ayuda a los estudiantes a desarrollar habilidades comunicativas que le permitan ser capaces de entender y asimilar el idioma, y comunicarse por ellos mismos de forma sencilla. Esta investigación se llevó a cabo en la escuela secundaria “Rolando Pedrosa Fernández” del poblado de Báez, municipio de Placetas. Para los efectos de esta investigación se utilizó un grupo de estudio, en el cual trabaja el autor, que sirvió tanto para el diagnóstico como para el posterior desarrollo del proceso de construcción. Para llevar a cabo esta investigación diferentes instrumentos y técnicas fueron utilizados teniendo en cuenta los diferentes métodos. La implementación práctica de algunos ejercicios comunicativos para desarrollar las habilidades de expresión oral en los estudiantes de 8vo grado fue llevada a cabo y esta mostró resultados positivos, alcanzando los objetivos para los que fueron originalmente diseñados. Teniendo en cuenta los elementos explicados previamente fue creado un manual complementario para recopilar todos esos ejercicios que fueron creados en la práctica a través del curso escolar para ayudar a los estudiantes a poner en práctica los contenidos aprendidos en clases. Este trabajo consiste de seis partes: Introducción, Desarrollo, Conclusiones, Recomendaciones, Bibliografía y Anexos.
Keywords: Enseñanza comunicativa; Inglés; Lenguas extranjeras; Educación Secundaria Básica; Habilidades; Expresión oral